2005
DOI: 10.1590/s0101-41612005000400006
|View full text |Cite
|
Sign up to set email alerts
|

A computable general equilibrium model to analyze distributive aspects in Brazil with a trade policy illustration

Abstract: This paper presents a Computable General Equilibrium model specified to simulate the policy impacts on income distribution in Brazil, with complex and systemic propagation methods. To capture the distributive impacts, the model adopts a design focused on the separation of production and institutional factors, as labor and households. The model has three blocks: product and factor markets, and a block that handles with income transfers among institutions. The labor market specification incorporates a recent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The full description and data for these programs are presented in Cury et al (2010, Appendix D). The CGE model used in this research is an extension of the one presented by Cury et al (2005), where further details can be found, and is a result of a series of developments made in the model proposed by Devarajan et al (1991), as can be seen in Cury (1998), Barros et al (2000) and Coelho et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…The full description and data for these programs are presented in Cury et al (2010, Appendix D). The CGE model used in this research is an extension of the one presented by Cury et al (2005), where further details can be found, and is a result of a series of developments made in the model proposed by Devarajan et al (1991), as can be seen in Cury (1998), Barros et al (2000) and Coelho et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…The CGE model used here is an extension from the one presented by Cury et al (2005) 15 where further details can be found.…”
Section: The Cge Model -Main Featuresmentioning
confidence: 99%
“…29 A brief description of wage curves can be found in Cury et al (2005). Broader explanation about them can be found in Oswald (1990, 1994 …”
Section: The Labor Marketmentioning
confidence: 99%
“…Regarding their application, CGE models have been used by diverse authors for different purposes. Among those who utilise the CGE model for the analysis of income redistribution are the works of Cury et al (2003), Kim and Kim (2002), Bye and Avitsland (2002) and Güzel and Kulshrestha (1995).…”
Section: Introductionmentioning
confidence: 99%